Breaking the Net : Family Structure and Street-Connected Children in Zambia - Strobbe, Francesco; Olivetti, Claudia; Jacobson, Mireille (Taylor and Francis, 2013)
Drawing on original fieldwork in the slums of Ndola in Northern Zambia we isolate those features of a child's nuclear and extended family that put him most at risk of ending up on the streets. We find that older, male children and particularly orphaned children are more likely to wind up on the street. Families with a male household head who is in poor health are more likely to originate street-connected children. In contrast, households with surviving maternal grandparents or with a male head who has many sisters are significantly less likely to originate street-connected children.